Perbandingan Volume Rangka Kayu Pada Pembuatan Rangka Atap Kuda-Kuda Bentang 8 (Delapan) Meter Berdasarkan SNI 7973-2013 - Darmawan, Rizqi; Husni, Hasti Riakara; Widyawati, Ratna (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
AbstractThe roof frame is a building structure that is above ringbalk. The roof frame serves as a retaining roof from pressure provided by the roof . Constructs of trusses are generally made of the same type and dimensions of wood use for short, medium, or long spans. Therefore, it needs analysis wood requirement of truss. This study aims to determine the dimensions and volumes of truss and compare volume of efficient timber requirements of the planned. In this research,volume requirement analysis of truss.The first, selection of wood used in the span of 8 meters. Then make 4 types of truss. Then, load analysis using SAP2000 to get the force. Having obtained value of force, then performed an analysis of the pull force and press so that the dimensions used are safe. Furthermore, the calculation of the volume of wood demand on each type of the planned, so that obtained efficient comparison volume of the 4 types.In the analysis, the dimensions of each type are type 1 (6/6 cm, 6/8 cm, 8/8 cm and 8/10 cm), type 2 (4/6 cm, 6/8 cm, and 8/8 cm), type 3 (4/6 cm and 6/8 cm) and type 4 (4/6 cm, 6/8 cm, and 8/10 cm). Then the volume of wood demand on type 1 (0,2038 m3), type 2 (0,1383 m3), type 3 (0,1229 m3), and type 4 (0,1797 m3). Based on the stem rod analysis, it was concluded that the most efficient roof truss type of the 4 types, namely the 3rd type.Keywords: Roof frames, truss, volume of wood